Freaky Friday [compact disc, unabridged] - Rodgers, Mary, 1931-2014 (Random House/Listening Library, 1996)
A thirteen-year-old girl gains a much more sympathetic understanding of her relationship with her mother when she has to spend a day in her mother's body.